Kajian Teknis Geometri Peledakan Di Pit 2 Banko Barat PT Bukit Asam Tbk, Tanjung Enim, Sumatera Selatan - Masyeba Evans Lubis; Irvani Irvani; Haslen Oktarianty (MINERAL, 2020)
PT Bukit Asam Tbk is one of the company that runs in coal mining at South Sumatera. One of the mining activity in PT Bukit Asam Tbk is overburden stripping using blasting method. The purpose of blasting method is to soften the hard outer layer material to ease the process of excavation using drilling and hauling instrument. Analysis of blasting geometry is done in order to get the fragmentation result that appropriate to the capabilities of drilling and hauling instrument. In the location of Pit 2 Banko Barat, blasting using air decking method that is called stemdeck is done to get better fragmentation result and less explosives usage. The research consist of 10 times blasting. The actual geometry rate here as follows 6.46 m burden, 6.40 m space, 6.75 hole depth. According to three data that are chosen in condition of same powder factor result in uneven fragmentation rate. This is caused by different rain intensity. Rainfall is causing blasting hole to be wet and decreasing the blasting capabilities of explosives. Those three explosives result in 18.22 cm of total fragmentation rate. This condition is caused by the same doing to different rock structure on mining location in the making of blasting geometry design. Fragmentation rate chart shows increasing value that follow burden value. Lowest fragmentation rate is 12.46 cm with 6.38 cm burden, 0.18 kg/m3 powder factor. So that if fragmentation needed to be lower than 12.46 cm later, it is recommended to use burden under 6.38 cm when calculating the blasting geometry design.